PUBLIC SERVICES MAL IN REALIZING BUREAUCRACY REFORM (CASE STUDY: PUBLIC SERVICES MAL IN PADANG CITY) - Ratih, Ratih; Putera, Roni Ekha; Koeswara, Hendri (Kebijakan : Jurnal Ilmu Administrasi, 2025)
This study aims to analyze the implementation of MPP in the city of Padang, seen form perspective of the New Public Service, which is measured from 4 variables of public service motivation offered by Perry and Wise. Public service motivation includes beliefs, values, and attitudes that go beyond personal interests and organizational interests so that later it will encourage an employee to provide satisfactory service. The research method used is qualitative case study with data collection techniques in the form of observation, interviews, and documentation. The results of the study show that the implementation of MPP Services in Oadang City has been enjoyed by the community, although not all services can be carried out by the community in the Padang City Public Service Mall building in accordance with the regulations that were in effect at the beginning of the policy implementation, it was marked that only 5 agencies opened services at MPP Padang City. The findings of this study when analyzed using PSM theory have not been considered effective and efficient because if measured form the motivatiob of public service, especially the variable of implementing commitmen, it is still not running optimally as indicated by the availability of human resources, budget and facilities at MPP in Padang. Based on that, the Padang city DPMPTSP needs to increase the number of human resources, budgets, and available facilities and apply adaptive service to MPP according with the current pandemic condition.